2015
DOI: 10.1539/joh.15-0068-ra
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive disorders in hairdressers and cosmetologists: a meta‐analytical approach

Abstract: small for gestational age, which had an RRc of 1.24 (95 CI%: 1.10−1.41); low birth weight, which had an RRc of 1.21 (95% CI: 1.06−1.39); and embryonic and fetal losses, which had an RRc of 1.19 (95% CI: 1.03−1.38). Conclusions: This work confirms a weak increase in risk of some reproductive disorders in female hairdressers/cosmetologists. However, the evidence level is rather weak, and a causal association between job and reproductive outcomes cannot be asserted. (J Occup Health 2015; 57: 485−496)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…For example, studies have shown that parental employment in agriculture may contribute to stillbirth and increase the risk of congenital malformations and organ-system defects in their offspring [4,5]. The nursing profession, or work as a hairdresser or cosmetologist have been associated with several adverse pregnancy outcomes [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that parental employment in agriculture may contribute to stillbirth and increase the risk of congenital malformations and organ-system defects in their offspring [4,5]. The nursing profession, or work as a hairdresser or cosmetologist have been associated with several adverse pregnancy outcomes [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focused on the effects of occupational exposure to chemical substances which persist in hair care products on abnormal birth outcome and maternal complications in hairdressers [ 20 22 , 26 29 ] and compared with salesclerks[ 21 , 30 32 ], but the results are inconsistent. A meta-analysis showed hairdressers and cosmetologists had a significant increased risk of neonatal complications, such as LBW, fetal loss, SGA (small for gestational age) [ 33 , 34 ]. Our results showed women customers who used hair dye pre-pregnancy had high risk of LBW (OR adjusted = 1.71, 95% CI: 1.01–2.92).…”
Section: Discussionmentioning
confidence: 99%
“…15,22,[24][25][26][27][28]31,32 They found that, in general, toxicological results are not sufficient to establish a link between cosmetic exposure and reproductive disorders among French hairdressers for common cosmetic products such as shampoos, waving products and hair dyes. 30 However, when the Margin of Safety (MoS) was evaluated for several hair dyes, the results showed that nearly 37% of cosmetic products considered as safe for consumers should be considered as potential risk products for professionals. 33 It should be noted that in this work, the systemic exposure dose (SED) had to be assessed using upper values for the frequency of use for cosmetic products due 5 to the lack of data.…”
Section: Scientific Committee On Consumer Safety (Sccs) This Committmentioning
confidence: 99%